Living Conditions in Rural Areas in Romania From 1990 to 2020 - Stănescu, Iulian (Calitatea Vieții, 2021)
The paper looks into the main trends of living conditions in rural areas in Romania from 1990 to 2020. The first part of the paper deals with housing. It features issues and indicators concerning housing supply, the breakdown of the housing stock by building material, overcrowding, vulnerable groups, and housing cost overburden. The second part focuses on access to public utilities: water, sanitation, natural gas, electricity and the Internet. The third part looks into the policy and financing concerning living conditions in rural areas. We use national time series, objective data from census and statistical surveys for observing long term trends. Cross-sectional, objective data from European statistical surveys is used for international comparisons. According to the main findings, living conditions in rural areas in Romania experienced a marked improvement over the thirty year period, especially in terms of reduced housing overcrowding, increased access to water, sanitation, and the Internet. However, this statement requires nuances and caveats. Despite the progress made, the gap compared to Western Europe persists. The suburbanisation of rural areas and the variance between and within communes in terms of dwellings’ access to water, sanitation, and natural gas are two trends that point to the increased heterogeneity of rural communities in Romania. Looking forward, there are sustainability and affordability risks concerning the expansion of public utilities in rural areas.